Research and design voice control camera using raspberry PI - Janani, V.; Puviarasi, R.; Ramalingam, Mritha; Boselin Prabhu, S. R. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Today we are building a valuable venture in which we can control the LED lights utilizing our voice through Smart Phone. In this undertaking, we will send voice directions from Smart Phone to Raspberry Pi utilizing Bluetooth Module and Raspberry Pi will get that transmitted flag remotely and will perform separate assignment over the equipment. We can supplant the LEDs with the AC home machines utilizing transfers and can fabricate a Voice Controlled Home Automation Project. This paper basically worried about the programmed voice control of light or some other home machines. It is utilized to spare the electric power and human vitality. This task is made with assistance of Raspberry Pi 3 and Relay driver circuit. The different machines are associated with the transfer circuit and the mouthpiece associated with Raspberry Pi 3. After fruitful acknowledgment of voice direction the Raspberry Pi 3 drives the comparing machines. Voice acknowledgment is created by utilizing Google API's.